CCNDBP1, a Prognostic Marker Regulated by DNA Methylation, Inhibits Aggressive Behavior in Dedifferentiated Liposarcoma via Repressing Epithelial Mesenchymal Transition - Yang, Lingge; Wu, Zhiqiang; Sun, Wei; Luo, Peng; Chen, Shiqi; Chen, Yong; Yan, Wangjun; Li, Yan; Wang, Chunmeng (Frontiers in Oncology, 2021)
The present study aimed to explore the prognostic value, function and mechanism of CCNDBP1 in dedifferentiated liposarcoma (DDL). Immunohistochemistry staining was used to analyze the protein expression of CCNDBP1 in tissue specimens. After silencing CCNDBP1 in LPS853 and overexpressing CCNDBP1 in LPS510, CCK-8, clone formation, transwell migration and invasion assays were used to detect cell proliferation, migration, and invasion ability. CCNDBP1-induced cell apoptosis was analyzed by flow cytometry. The altered expression of epithelial-mesenchymal transition (EMT)-related proteins were detected by Western blot. The methylation, gene expression, and clinical data of 58 samples with DDL were analyzed using the cancer genome atlas (TCGA) database. Low expression of CCNDBP1 was associated with poor prognosis of patients with DDL and was considered an independent prognostic factor of progression-free survival (PFS). CCNDBP1 significantly inhibited the clone formation, proliferation, migration, and invasion of cancer cells in vitro and promoted cancer cell apoptosis. CCNDBP1 could repress the pathological EMT, thereby inhibiting the malignant behaviors of DDL cells. The high degree of DNA methylation sites cg05194114 and cg22184989 could decrease the expression of CCNDBP1 and worsen the prognosis of DDL patients. This is the first study reporting that CCNDBP1 is a tumor suppressor gene of DDL and putative prognostic marker in DDL patients. CCNDBP1 might inhibit the ability of cell proliferation and invasion by repressing pathological EMT, and the expression of CCNDBP1 could be regulated by DNA methylation in DDL.